RANCANGAN SISTEM PAKAR PENANGANAN PERANGKAT JARINGAN KOMPUTER - Miwan Kurniawan Hidayat (LPPM Universitas Bina Sarana Informatika, 2012)
The role of an expert or experts is crucial in solving a problem so as to get an effective solution. Currently there is a new innovative techniques in capturing and integrating knowledge of an expert in a computer system. In the expert system are the knowledge base in the form of formal knowledge, which mostly comes from experience. Like humans theoretical and practical knowledge and has been refined through experience in the domain. The use of expert system can apply or pour the expertise of a technician or an expert in the field of computers, especially computer networks. The purpose of this study is to design an expert system computer network management device that acts to solve practical problems when the expert is not available. In this research, the analysis and design of data structures of production rules, inference mechanism in tracking conclusion based knowledge base and the user interface. Expert systems are designed to provide solutions based on production rules by using a forward chaining inference mechanism for identifying and advising solutions to the problem of computer network devices.Keywords: expert systems, artificial intelligence, computer network.